(untitled) (Journal SCIENCEVOLUTION, 2024)
This article explores the possibilities following the impact that Generative Artificial Intelligence, especially ChatGPT, has had on education and research, focusing on Systematic Literature Reviews (SLR) according to the PRISMA method. It analyzes how ChatGPT can assist in the identification and selection of literature, data extraction and synthesis, and the evaluation of study quality. The discussion also covers the potential of Generative AI to enhance learning, personalize education, and formative and summative assessment. In addition, it reflects on the ethical challenges and necessary precautions when integrating these technologies into research practices. It concludes that while ChatGPT offers significant opportunities for efficiency and quality in SLRs, careful and ethical use is essential, highlighting the importance of proper citation and transparency in its application.